The Appropriateness of Conciliation/Mediation for Sexual Harassment Complaints in New Zealand - Baylis, Claire (Victoria University of Wellington Law Review, 1997)
In this article, Claire Baylis examines the statutory models of mediation/conciliation in the Human Rights Act 1993 and the Employment Contracts Act 1991 which are used for sexual harassment complaints. She argues that the practice of mediating these complaints is inappropriate due to the incompatibility of the cha585he specific characteristics of most sexual harassment complaints. Further, an analysis of the actual dispute resolution provisions under the Acts raises other issues in the sexual harassment context. Finally, the author outlines some possible reforms to dispute resolution processes in this area.